SISTEM INFORMASI INVENTORY OBAT BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER DI APOTEK PUSPITA FARMA SEMARANG - Khoirur Rozikin; Abdul Jamil; Iman Saufik Suasana (LPPM Politeknik Pratama Kendal, 2022)
Technological developments within a company are needed in the execution and evaluation of all existing jobs so that the work becomes fast, precise, and accurate. Puspita Farma Pharmacy is one of the community service businesses engaged in the sale of medicines. The high level of service to the community causes errors in processing and making reports which are still done manually. The process of recording goods report data using two kinds of record books, namely a daily goods order book, a daily goods sales recap book, and a record book for each purchase of goods. The use of this manual system found many obstacles that caused the work process to be ineffective and efficient, including errors in recording incoming and outgoing drug data, resulting in empty or excessive drug supplies and the discovery of expired drugs. As a solution to the problems currently experienced by the Puspita Farma Pharmacy, it is necessary to create a drug inventory information system at the Puspita Farma Pharmacy. This information system was created using the PHP programming language, Mysql for databases and the Codeigniter framework for data processing.